Sequence comparison of human and yeast telomeres identifies structurally distinct subtelomeric domains. - Flint, J; Bates, G; Clark, K; Dorman, A; Willingham, D; Roe, B; Micklem, G; Higgs, D; Louis, E (1997)
We have sequenced and compared DNA from the ends of three human chromosomes: 4p, 16p and 22q. In all cases the pro-terminal regions are subdivided by degenerate (TTAGGG)n repeats into distal and proximal sub-domains with entirely different patterns of homology to other chromosome ends. The distal regions contain numerous, short (<2 kb) segments of interrupted homology to many other human telomeric regions. The proximal regions show much longer (approximately 10-40 kb) uninterrupted homology to a few chromosome ends. A comparison of all yeast subtelomeric regions indicates that they too are subdivided by degenerate TTAGGG repeats into distal and proximal sub-domains with similarly different patterns of identity to other non-homologous chromosome ends. Sequence comparisons indicate that the distal and proximal sub-domains do not interact with each other and that they interact quite differently with the corresponding regions on other, non-homologous, chromosomes. These findings suggest that the degenerate TTAGGG repeats identify a previously unrecognized, evolutionarily conserved boundary between remarkably different subtelomeric domains.